Factors Influencing Residents' Psychological Status During Standardized Training in COVID-19 - Xiang, Dongfang; Liang, Bao; Wang, Yongyi; Li, Biao; Peng, Juan; Zhang, Sheng; Chen, Bei; Yan, Chuandong; Xu, Chao (Frontiers in Psychiatry, 2021)
Objectives: To explore the influencing factors of residents' psychological status during standardized training in COVID-19 for finding ways to promote their mental health. Methods: A total of 760 residents were surveyed with a structured questionnaire. Correlation analysis was used to analyze the influencing factors of psychological status of the residents, and a mediation model was constructed to verify the mediating role of satisfaction. Results: Age, willingness to study medicine, and satisfaction were positively correlated with negative psychological status (P < 0.05). And gender, only child or not, and annual household income (RMB) were negatively correlated with negative psychological status (P < 0.01). Residents' satisfaction with standardized training mode plays a complete mediating role between annual household income and negative psychological status. Conclusions: Our findings emphasize the importance of concentrating on resident's psychological status and family economic situation. And relative departments should take action to optimize the standardized training mode to improve the satisfaction.